PENAMBAHAN NANOKALSIUM TULANG IKAN NILA (Oreochromis niloticus) TERHADAP KARAKTERISTIK FISIKOKIMIA KERUPUK UDANG - Fatoni, Muhammad Ali; Sumardianto, Sumardianto; Purnamayati, Lukita (Jurnal Teknologi Hasil Pertanian, 2021)
Shrimp crackers are a type of dry food made from tapioca flour, shrimp and other additives. Shrimp crackers with the addition of fish bone flour nanocalcium is an alternative food that can be developed as a source of calcium. The purpose of this study was to determine the effect of adding nanocalcium tilapia bone flour to physico-chemical characteristics and the best concentration of tilapia nanocalcium bone in shrimp crackers to be accepted by panelists. This study used a Completely Randomized Design (CRD) with one factor, namely the concentration of addition of tilapia nanocalcium bone, namely 0%, 5%, 10%, and 15% which was done 3 times. Data were analyzed using ANOVA and continued by Tukey test if there were significant differences. The results showed that the addition of tilapia nanocalcium bone significantly affected the increase in the ash and calcium levels of shrimp crackers, while the water content, protein and developmental power decreased with the addition of increasing tilapia bone nanocalsium. The addition of 10% tilapia bone nanocalcium is the best concentration based on panelist acceptance with the category of very fond of the parameters of smell, taste, and texture, while for the panelist appearance parameter accepts in the like category. Shrimp crackers with the addition of 10% nanocalcium contain 10.76% water content; ash content 13.81%; protein content 2.40%; 2.12% calcium content and 42.62% swelling power.